Mobile app development for classroom event management - Ong, Tze Yong (Nanyang Technological University, 2020)
As of the writing of this paper,many schools and institutions such asNanyang Technological University (NTU) continue to take attendance for classroom events like tutorials, tests and examinations the traditional way by physically marking an attendance sheet. This can become time-consuming as the number of attendees for an event increase. This paper explores the design and development of a classroom event management application running on Android-based smartphones that will allow users to plan classroom events, set up a user registration database and perform event attendee registration and processing in real time. The application will be run on an NFC-enabled smartphone that will also function as a reader for contactless smart cards for identification and registration of each participant. The design and development of a working prototype will be covered, including the design of the database and functions of the application. Effectiveness and limitations will be discussed, along with alternative methods and potential future development.